The influence of Pfannenstiel and midline incisions to the wound condition on the third day post gynecologic surgery - Ibnu Pranoto, Nita Tri Kurniati Sulchan Sofoewan (Universitas Gadjah Mada, 2012)
Many factors should be considered by a surgeon to choose an abdominal incision, such asÂ incision extensibility, speed of operation, presence or absence of adhisions, hemostasis problems,Â possibility of postoperative complications such as infections, hernia or dehiscence, and woundÂ healing. Midline or linea mediana incision makes the field operation seem wider, therefore theÂ operations can be performed more uickly. Meanwhile, transverse incision such as Pfannenstielincision is gaining popularity with the less incidence of infection, hernia, and wound dehiscenceÂ because this technique follows Langerâs lines resulting in reduced traction at the skin edges andÂ making better wound closure and approximation. This study aimed to evaluate the influence ofPfannenstiel and midline incisions to the wound condition on the third day post gynecologicÂ surgery. This was an observational study using a prospective cohort study design. The subjectsÂ were patients with the indications for gynecologic surgery in Dr. Sardjito General HospitalYogyakarta and affiliated hospitals who fulfilled the inclusion and exclusion criteria. Sixty subjectsÂ were divided into two groups i.e. 30 subjects who underwent Pfannenstiel incision as treatmentÂ group and 30 subjects who underwent linea mediana incision as control group. The characteristicsof subjects of both group were not significantly different. No significant difference of theÂ wound condition on the third day after surgery between subjects who underwent PfannenstielÂ and linea mediana incisions was observed in this study (p=0.212). The risk of the wound beingnot dried yet on the third day after sugery on subjects who underwent linea mediana incisionÂ technique was 2.5 times higher compared to subjects who underwent Pfannenstiel incisionÂ technique. However, it was not statistically different (p= 0.212; RR= 2.5; 95%CI= 0.525-11.894). In conclusion, there is no significantly different effect of Pfannenstiel and linea medianaÂ incisions to the wound condition on the third day post gynecologic surgery.Keywords: Pfannenstiel incision - midline incision - wound healing - gynecologic surgery -complication